Identification of viruses and screening of summer squash (Cucurbita pepo) germplasm against viral disease under controlled conditions - SHARMA, MANJU; THAKUR, P D; GUPTA, DHARMESH; THAKUR, A K (The Indian Journal of Agricultural Sciences, 2026)
Two representative isolates (C-I and C-II) of virus infected summer squash from Himachal Pradesh were characterized and identified on the basis of their symptomatology, transmission, biophysical properties, particle morphology and serology. Isolate C-I exhibited characteristic symptoms of mosaic, inward rolling and cupping of leaves and ringspots on the surface of fruits, whereas C-II isolate produced vein clearing, mosaic, blistering and shoe-stringing in addition to wart like protrusions on fruits. Both the isolates were transmissible through sap and aphid vectors Myzus persicae and Aphis craccivora.. Biophysical properties of C-I and C-II included TIP of 65-70,oC and 55-60oC, DEP of 10-4 -10-5 and 10-310-4 and LIV of 10 and 5 days at room temperature and 15 and 8 days at refrigeration conditions, respectively. Serologically, C-I and C-II isolates reacted positively with antiserum of CMV and ZYMV, respectively in ELISA tests. Morphologically, C-I had isometric particles of 28.5 nm, whereas C-II had flexuous rods measuring 760x11 nm. C-II isolate was also successfully detected in RT-PCR assay by using potyvirus group specific primers (P9502 and CPUP) and desired amplicon of 700 bp was obtained. Hence, based on these identification parameters, C-I and C-II isolates have been identified to be similar to CMV (cucumovirus) and ZYMV (potyvirus), respectively. Forty one varieties/collection/lines of Cucurbita spp including summer squash (15) and pumpkin (26) were evaluated in glasshouse conditions against CMV and ZYMV viruses to find out the source (s) of resistance. None of varieties/ collections/lines of C. pepo tested were resistant to infection of CMV and ZYMV but seven local collections of C. moschata were found highly resistant to both the viruses under glasshouse conditions.